Foregut duplication cyst of the stomach - ÇELİKEL, ÇİĞDEM; YEGEN, BERRAK (My University, 2008)
Foregut duplication cyst of the stomach is an extremely rare disease entity. A 35-year-old Korean man presented with epigastric pain. An abdominal cystic mass, measuring 7 ¥ 6 ¥ 5 cm, was found in the lesser curvature of the stomach. The cyst was unilocular with a grey-white, rubbery wall. Microscopically, the cyst wall was lined by pseudostratified ciliated, columnar epithelium and gastric mucosa with a complete lining of smooth muscle bundles. Although the origin of this lesion remains uncertain, this case suggests that the gastric cyst arose from the embryonic foregut and showed differentiation toward respiratory and gastric structures.
Keywords: Tıp; Histoloji-Embriyoloji; Cerrahi Tıp Bilimleri; Patoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Biyokimya; Temel Bilimler; Medicine; Histology and Embryology; Surgery Medicine Sciences; Pathology; Life Sciences; Molecular Biology and Genetics; Health Sciences; Fundamental Medical Sciences; Biochemistry; Natural Sciences; HÜCRE BİYOLOJİSİ; Yaşam Bilimleri (LIFE); PATOLOJİ; Biyoloji ve Biyokimya; CELL BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); PATHOLOGY; BIOLOGY & BIOCHEMISTRY; Patoloji ve Adli Tıp; Histoloji; Biyokimya (tıbbi); Moleküler Biyoloji; Hücre Biyolojisi; Pathology and Forensic Medicine; Histology; Biochemistry (medical); Molecular Biology; Cell Biology; foregut duplication cyst; stomach